2018
DOI: 10.1002/bbb.1884
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the potential production of methane and chemicals using anaerobic digestion

Abstract: The aim of this paper is to calculate the amount of energy or chemicals that can be produced using anaerobic digestion (AD). Five feedstocks were considered: the organic fraction of municipal solid waste (OFMSW); cattle, pig and poultry manure; energy crops; agricultural residues, and sewage sludge. Carbohydrates, proteins, and lipids were assumed to be the biodegradable components of the feedstocks. Chemical oxygen demand (COD) was assumed as a basis for the calculations of the production of methane and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…(10), were considered to be the sum of the Model SC and of the carbohydrates in the variables X S , X, X I . For X S , the carbohydrates were calculated by dividing X S by the COD conversion factor for cellulose (1.185 gCOD g −1 cellulose), for X and X I the carbohydrates were calculated assuming that the microorganisms dry weight is made of 27% carbohydrates [3]:…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(10), were considered to be the sum of the Model SC and of the carbohydrates in the variables X S , X, X I . For X S , the carbohydrates were calculated by dividing X S by the COD conversion factor for cellulose (1.185 gCOD g −1 cellulose), for X and X I the carbohydrates were calculated assuming that the microorganisms dry weight is made of 27% carbohydrates [3]:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…However, AD could also be used in a biorefinery context to produce chemicals such as short-chain organic acids, ethanol, and hydrogen, which are intermediates in the digestion process [1,2]. According to recent studies [3,4], most of the potential of AD for the generation of energy is still undelivered. Indeed, on a global scale AD generates less than 1% of the electricity it could potentially generate based on the available feedstocks and, in the UK, only 19% of the AD potential is being delivered.…”
Section: Introductionmentioning
confidence: 99%
“…The global agricultural residue production from six key crops (barley, wheat, maize, soybean, rice, and sugar cane) was estimated as 3.7 Gt dry matter (DM) per year for the period 2006-2008 (Bentsen et al, 2014). Other studies reported global generation rates of 4.5-4.7 Gt DM/yr from 13 crops in 2014 (Dionisi et al, 2018) and 5 Gt DM/yr from 26 crops in 2013 (Cherubin et al, 2018). Kim and Dale (2004) estimated that 1.5 Gt of crop residue is available for conversion to bioethanol from seven crops comprising of corn, barley, oat, rice, wheat, sorghum, and sugar cane.…”
Section: Introductionmentioning
confidence: 99%
“…According to our recent study [3], on a global scale, the current energy generation by anaerobic digestion is only a minor fraction of the total potential energy that could be generated based on the generation rate of organic waste. One of the limitations in the use of anaerobic digestion for energy or chemicals production is the lignocellulosic nature of many types of organic waste (e.g.…”
Section: Introductionmentioning
confidence: 99%